1995
DOI: 10.1007/bf00193698
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of residual nephrons to high dose furosemide described by diuretic efficiency

Abstract: Ten haemodialysis (HD) patients with a median residual creatinine clearance (CLCR) of 1.9 ml.min-1 x 1.73 m-2 (range 0.6-5.3) were treated with oral furosemide (F) 2.0 g. Overall-efficiency (O-E, daily sodium excretion/total urinary F) and total-efficiency (delta-E, increase in daily sodium excretion/total urinary F) were measured on the last 24 hours of each interdialysis interval. In addition, O-E was measured during the complete interdialysis interval in 10 HD patients with a median CLCR of 5.6 ml.min-1 x 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
(26 reference statements)
1
9
1
Order By: Relevance
“…In contrast to what had been observed in other studies [11,21], which acutely encountered an increase in FENa after furosemide use, our study has not encountered a statistically significant difference between FENa in the DG and NDG (p = 0.91, Table 3). In contrast to studies acutely using high doses of diuretics for short periods of time, the patients in our study had been using diuretics chronically, with small doses of furosemide for at least 5 months, and had normal sodium ingestion.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…In contrast to what had been observed in other studies [11,21], which acutely encountered an increase in FENa after furosemide use, our study has not encountered a statistically significant difference between FENa in the DG and NDG (p = 0.91, Table 3). In contrast to studies acutely using high doses of diuretics for short periods of time, the patients in our study had been using diuretics chronically, with small doses of furosemide for at least 5 months, and had normal sodium ingestion.…”
Section: Discussioncontrasting
confidence: 85%
“…Our study showed that GFR was similar in the DG and NDG (p = 0.07, Table 3); however, the mean values for GFR could have been similar due to the reduced number of patients in each group. As per van Olden et al [21], our data has shown this correlation that patients with higher UVNa present higher GFR (p = 0.0004, r = 0.73, Fig. 3).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In clinical practice, furosemide is administered repetitively to shift the pathological homoeostasis (water, sodium balance; oedematous state associated with congestive heart failure) of the body in cardiac failure or decompensatio cordis. Repetitive intravenous administration of furosemide results in a gradual decrease in urine and sodium output (Kaissling et al 1985;Gerlag & VanMeyel 1988;Brater 1991;Lahav et al 1992;VanOlden et al 1992VanOlden et al , 1995. The diuretic as well as the post-diuretic effect (rebound effect) add to the overall effect of dehydration upon repetitive dosing (Copeland et al 1983;VanMeyel et al 1994;Kang et al 1995).…”
Section: Repetitive Dosingmentioning
confidence: 99%
“…These high dosages do increase the residual diuresis in the short term. During long-term treatment this effect wears off (Gerlag & VanMeyel 1988;Brater 1991;VanOlden et al 1992VanOlden et al , 1995. Furosemide has sig-ni®cant renal and extrarenal haemodynamic effects in congestive heart failure (Dikshit et al 1973;Brater et al 1980).…”
Section: Impaired Kidney Functionmentioning
confidence: 99%